'My nose is running like a pound of butter': exploring young children's humour. Issue 13 (2nd October 2020) - Coates, Elizabeth; Coates, Andrew
ABSTRACT: This paper sets out to explore the nature of the humour generated when pairs of young children talk and draw together. Emphasis is on children's use of language since most of our humorous instances are expressed verbally rather than visually. Humour's various features proved to be highly complicated, however, as examples often transcend boundaries, so in order to facilitate debate our findings were classified and discussed under the following headings: preposterous statements, exaggeration and humorous anecdotes; telling jokes; singing and chanting, playing with words, and rhyming and repeating; bodily functions, body parts and nakedness; narrative humour related to drawing. Although we found many common elements, humour, in terms of its development and progression, appeared to depend on an increasing ability to manipulate language, a deepening understanding of the cultural context in which children lived and overall, a particularly strong sense of the absurd.